Impact of the mHealth strategy in sodium consumption markers: AvaliaSal Study - Silva PORTO, Aline; Xavier MARTINS, Haysla; Perim de FARIA, Carolina; Bisi MOLINA, Maria del Carmen (Revista de Nutrição, 2023)
Objective Evaluate the effectiveness of mHealth strategy on sodium consumption markers. Methods Intervention study carried out with 175 adults (20-59 years), from an educational institution of Vitória, Espírito Santo State. Participants were made aware through posters, oral approach and electronic media. Anthropometric, hemodynamic, socioeconomic, health, and dietary practices data was collected in two stages. After the first assessment, participants were randomized into two groups: Intervention Group and Control Group. The Intervention Group included 21 electronic messages and 3 videos on healthy eating focusing on the goal to reduce sodium intake for 3 months. Behavioral changes were assessed using the Generalized Estimation Equation (p-value <0.05). Results At baseline, no significant differences in socioeconomic, anthropometric and health variables, and eating practices between groups were observed. The stock broth cube was the most used ready processed seasoning. After the intervention, a reduction in the use of stock broth was observed only in the intervention group (β=0.615; p=0.016). In addition, 73% of the intervention group participants reported that the messages were clear, 67% reported that they were useful, and 48% stated they followed the guidelines. Conclusion There was a reduction in the frequency of use of stock broth cubes, demonstrating the potential effect of the m-Health strategy on sodium consumption markers in individuals without a hypertension medical diagnosis.